Ask me anything: Michelle Simmons. (January 2021) - Durrani, Matin
Abstract : Michelle Simmons is director of the Centre of Excellence for Quantum Computation and Communication Technology at the University of New South Wales, Australia. A pioneer in atomic-scale silicon devices, she has built the world's smallest transistor, the narrowest conducting wires, 3D atomic electronics and the first two-qubit silicon gate. In 2018 Simmons was named Australian of the Year.